Penyediaan Fasilitas Perpustakaan Sekolah (Studi Tentang Minat Baca Siswa Di Sekolah Menengah Kejuruan Negeri (SMKN) 4 Malang) - Ayuwigati, Roositha (Jurnal Administrasi Publik, 2016)
Abstract: Provision of School Library Facilities (Study about Student’s Reading Interest at State Vocational School (SMKN) 4 Malang). Reading interest of students in the school could be seen from the library utilization as a means of reading which has an obvious source of the information. In Indonesia, the school library is obliged to have the building and room facilities, collection facilities, search facilities, and service facilities in accordance with national standards library. State Vocational High School (SMKN) 4 Malang has a library that follows national standard library. In the 2014-2015 school years the library had only 40% of visitors and 30% of borrowers. This research was conducted to describe and analyze standardization the provision of SMKN 4 Malang library facilities in accordance with national standard library as well as to describe and analyze the SMKN 4 Malang student’s reading interest in the utilization of library. The results showed that the building and room facilities has the leak on the roof of the building while the collection facilities has far below 30% of a fiction collection. Meanwhile other facilities such as search facilities and service facilities are already comply national stamdard library. Furthermore, student’s reading interest which assessed by the frequency of visits and the frequency of loan collection may be expressed low. Students relatively rarely use the library as their reading means. Keywords : library facilities, student’s reading interest, SMKN 4 Malang   Abstrak: Penyediaan Fasilitas Perpustakaan Sekolah (Studi Tentang Minat Baca Siswa di Sekolah Menengah Kejuruan Negeri (SMKN) 4 Malang. Minat baca siswa disekolah dapat terlihat dari pemanfaatan perpustakaan sebagai sarana membaca yang jelas sumber informasinya. Di Indonesia perpustakaan sekolah wajib memiliki fasilitas gedung dan ruang, fasilitas koleksi, fasilitas penelusuran, dan fasilitas layanan yang sesuai dengan standar nasional perpustakaan. Sekolah Menengah Kejuruan Negeri (SMKN) 4 Malang memiliki perpustakaan yang mengikuti standar nasional perpustakaan. Pada tahun ajaran 2014-2015 perpustakaan hanya memiliki 40% pengunjung dan 30% peminjam. Penelitian ini dilakukan untuk mendeskripsikan dan menganalisis standarisasi penyediaan fasilitas perpustakaan SMKN 4 Malang sesuai standar nasional perpustakaan serta untuk mendeskripsikan dan menganalisis minat baca siswa SMKN 4 Malang dalam pemanfaatan perpustakaan. Hasil penelitian menunjukan bahwa fasilitas gedung dan ruang terjadi kebocoran pada atap gedung sementara fasilitas koleksi memiliki koleksi fiksi masih jauh dibawah 30%. Sementara dua jenis fasilitas lainnya yaitufasilitas penelususran dan fasilitas layanan dinilai sudah memenuhi standar. Selanjutnya minat baca siswa yang dinilai melalui frekuensi kunjungan dan frekuensi peminjaman koleksi dapat dinyatakan rendah. Siswa tebilang jarang memanfaatkan perpustakaan sebagai sarana membaca mereka.   Kata kunci: fasilitas perpustakaan,  minat baca siswa, SMKN 4 Malang